Percobaan Metode Sand Roasting Pada Daging Ayam Sebagai Pengganti Metode Roasting Konvensional Dalam Pembuatan Ayam Panggang Sehat - Maulana, Alifatqul (Jurnal Ilmiah Pariwisata, 2021)
The purpose of this research is how to cook food by burying the food with hot stones. The research method used in this study is an experimental research method. The research method used in this research is experimental research methods. The results of sand roasting will be tested using the organoleptic test to show differences in taste and texture between sand roasting and conventional roasting, namely oven roasting. The data used are primary data and secondary data. Primary data collection based on observation and assessment questionnaires. Meanwhile, the secondary is taken from various literatures and research journals. As a result, it took 75 minutes to find an effective and efficient sand roasting method. Based on the results obtained for the organoleptic test, there is no significant difference from the results of the sand roasting method with the oven roasting method. However, the sand roasting method is superior to oven roasting in terms of taste with a value of 3.04 for sand roasting and 2.96 for oven roasting. Likewise, in terms of texture, the sand roasting method is superior with a score of 3.08 while the oven roasting method scores 3.00. Keywords: Sand Roasting; Texture; Taste; Roast Chicken